Optimizing Sustainability: Exploring the Intersection of Carbon Trading and Social Forestry Initiatives - Girsang, Lode Wijk Pandapotan; Simbolon, Noviana; Saputri, Rizki Nanda; Lubis, Ria Karlina (Mahadi: Indonesia Journal of Law, 2024)
Carbon trading has emerged as a novel approach to mitigating climate change impacts and promoting sustainable development. The emphasis on social forestry enhances this strategy by involving local communities in forest management and carbon trading. In the context of the climate crisis, this study examines how the combination of carbon trading and social forestry can promote sustainability. The adoption of social forestry practices, such as empowering communities and managing forests sustainably, aims to reduce carbon emissions and preserve ecosystem health. This approach offers dual benefits by fostering local economic growth through carbon trading and safeguarding biodiversity while addressing climate change impacts. The research delves into the opportunities and obstacles of integrating carbon trading into social forestry, laying the groundwork for comprehensive solutions to sustainability and climate change adaptation.